1996
DOI: 10.1021/jp9614916
|View full text |Cite
|
Sign up to set email alerts
|

Excited State Energy Transfer Pathways in Photosynthetic Reaction Centers. 1. Structural Symmetry Effects

Abstract: Ultrafast excited state energy transfer to the primary electron donor or special pair in photosynthetic reaction centers has been measured following excitation of the lowest electronic state of the other chromophores. This was achieved by observing the rise time and induced anisotropy in the spontaneous fluorescence from the special pair using fluorescence up-conversion at 85 K. Very fast energy transfer is observed when exciting either of the bacteriochlorophyll monomers. Energy transfer from the bacteriopheo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
174
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(193 citation statements)
references
References 49 publications
17
174
2
Order By: Relevance
“…The fluorescence decay of P* was measured by fluorescence upconversion essentially as described. 94 Emission was detected at 890 nm at the magic angle relative to the excitation at 800 nm. RC samples had an OD of 0.6 at 800 nm in a 1 mm path length and contained 1 mM dithionite and terbutryn at 30 times the RC concentration to reduce Q A and displace Q B , respectively.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluorescence decay of P* was measured by fluorescence upconversion essentially as described. 94 Emission was detected at 890 nm at the magic angle relative to the excitation at 800 nm. RC samples had an OD of 0.6 at 800 nm in a 1 mm path length and contained 1 mM dithionite and terbutryn at 30 times the RC concentration to reduce Q A and displace Q B , respectively.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Between 10 and 40 scans were averaged for each sample. Each average was fit to the convolution of the pumpprobe cross correlation as determined the same day (typically between 150 and 170 fs) and a sum of exponentials, which included a fixed rise time of 150 fs due to the energy transfer from B* to P. 94 Picosecond Transient Absorption Spectroscopy. The transient absorption measurements were conducted basically as described previously 95 and utilized a regeneratively amplified Ti:sapphire laser pumping an OPA (Spectra Physics) to generate 130 fs excitation and white-light probe flashes at 10 Hz.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Energy transfer from 1 B to P as measured by the rise of emission from 1 P at 940 nm for 804 nm excitation is 163 ( 54 fs. 5 That the decay of emission at 850 nm matches the rise of emission from 1 P suggests that the excited state probed at 850 nm transfers energy to P. 15 Emission between 800 and 850 nm is observed for excitation in the H band at 760 nm in WT RCs at 85 K ( Figure 3B shows emission at 815 nm). The emitting state is populated with a lifetime of 85 ( 17 fs ( 1 H f B) and decays with a lifetime of 199 ( 16 fs ( 1 B f P).…”
mentioning
confidence: 91%
“…At room temperature P ϩ B A Ϫ is formed as a short-lived, intermediate with a lifetime of 0.9-1.5 ps (7)(8)(9)(10)(11). Charge separation is completed by electron transfer from P Until recently it generally was accepted that excitation of the RC bacteriopheophytins or monomeric Bchls resulted in downhill energy transfer to P within a few hundreds of femtoseconds, forming P* that drives charge separation (12)(13)(14)(15). However, steady-state fluorescence excitation experiments conducted at 77 K on mutant RCs in which P* has a very long lifetime have shown that, despite their rapidity, the efficiency of this energy transfer is not 100% (16,17).…”
mentioning
confidence: 99%